2020
DOI: 10.1111/ijcs.12627
|View full text |Cite
|
Sign up to set email alerts
|

Why is a picture ‘worth a thousand words’? Pictures as information in perceived helpfulness of online reviews

Abstract: The hybrid review format (verbal reviews accompanied by pictures) is increasingly prevalent in online consumer reviews. However, the mechanism behind the superiority effect of hybrid reviews is still unclear. Unlike previous studies based on information processing theory that emphasize the imagery-provoking ability of the verbal information, we contend that imagery in hybrid reviews is the information that adds more diagnostic value to online reviews and thus makes the reviews more helpful. Our experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 78 publications
0
39
0
1
Order By: Relevance
“…As the main source of visual stimuli for consumer products, a picture can quickly convey a unique advertising concept, clearly display the product features and effectively establish the brand image. And the information provided by pictures is often more expressive and specific (Wu et al., 2020). The visual appearance of product is critical determinant of consumer response and product success (Bloch, 1995).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main source of visual stimuli for consumer products, a picture can quickly convey a unique advertising concept, clearly display the product features and effectively establish the brand image. And the information provided by pictures is often more expressive and specific (Wu et al., 2020). The visual appearance of product is critical determinant of consumer response and product success (Bloch, 1995).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, pictures are important for communicating information about products and companies (Scott, 1994). Previous studies have shown that the use of images (compared with not using them) attracts consumers’ attention more easily (Miller & Stoica, 2004), makes online reviews tend to be perceived more helpful (Wu et al., 2020), helps the consumers to obtain and understand product information more quickly (Pennings et al., 2014), increases consumers’ recall of brand names and product information (Kisielius & Sternthal, 1984; Shepard, 1967), promotes consumers’ positive attitudes towards products, brands, advertisements and so forth, and increases consumers’ willingness to buy (Kroeber‐Riel, 1984; Mitchell & Olson, 1981; Rossiter & Percy, 1978).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In 2011, Lee et al conducted another experiment and found that OCRs with higher perceived credibility increase purchase intention (Lee et al, 2011). Moreover, Wu et al (2020) found that consumers rely more on OCRs with pictures, as they view pictures as an alternative explanation of reviews and tend to have a more favorable attitude toward these reviews.…”
Section: Jrim 162mentioning
confidence: 99%
“…Online consumer product review research has focussed primarily on product rating scales or text‐based reviews and found that these reviews can significantly influence consumer perceptions, attitudes and behaviour (e.g., Amblee & Bui, 2011; Chevalier & Mayzlin, 2006; Filieri & McLeay, 2014; Jang et al., 2012; Kostyra et al, 2016; Wang et al., 2012). A recent study on online consumer product reviews has, furthermore, shown that text‐based reviews are perceived as more helpful when augmented with images (Wu et al, 2021). Research on online consumer product reviews in video format, on the other hand, has been limited (Diwanji & Cortese, 2020).…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…The effectiveness of online product reviews has been shown to be affected by reviewer and content attributes, specifically message modality (Wu et al, 2021), content and style (Schindler & Bickart, 2012), valence, volume, and variance (e.g., Kostyra et al, 2016; Wang et al., 2015), source of the review (Dou et al, 2012; Forman et al., 2008), source credibility (Jin & Phua, 2014), parasocial interactions with reviewers (Lee & Lee, 2021) and level of detail and overall reviewer agreement (Jiménez & Mendoza, 2013).…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%